Prevalence and Risk Factors of Self-Medication Among the Pediatric Population in China: A National Survey - Yuan, Jing; Du, Wandi; Li, Zhiping; Deng, Qiao; Ma, Guo (Frontiers in Public Health, 2022)
Background: Self-medication of antibiotics is common in China, while the self-medication of other medicines is still unknown, especially for the younger children who are vulnerable to adverse drug events. The aim of this study was to estimate the prevalence of self-medication reported by parents among children under age 12 in China. Methods: A national cross-sectional survey was conducted among parents of children under age 12 in China, by using a self-administered online questionnaire. Parents were asked whether they have self-medicated their children in the past 12-month. Logistic regression analysis was performed to access the risk factors of self-medication. Results: Eligible questionnaires were obtained from 4,608 parents. The majority of respondents were mothers, aged between 30 to 39 years old, and held a college degree. A total of 1,116 (or 24.21%) respondents reported self-medication in the previous year. In the logistic regression model, parents with graduate degrees were less likely to self-medicate their children (Adjusted Odds Ratio [AOR] = 0.436; 95% Confidence Interval [CI] =0.296-0.641). The Odds of self-medication were associated with being father, living in Northern China, having a child at age 6-11, even though not reaching statistical significance. Conclusions: Our findings indicate that self-medication are common in children under age 12, highlighting the drug safety issue in China. It seems that the educational level is the risk factors of self-medication. More targeted intervention and educational program should be implemented to improve drug safety.